Comprehensive Analysis of Fundamental Concepts in Social Sciences: An Interdisciplinary Approach to Examining Society and the Environment - Rina Minita Gusliana; Delmira Syafrini (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2026)
This article aims to present the basic concepts of Social Science (IPS) as an interdisciplinary study that combines various disciplines, such as history, sociology, geography, and economics, to better understand the dynamics of society and the environment. Through this approach, the article provides insights into the importance of a comprehensive understanding in addressing complex social issues. This research uses library research methods, which involve a series of activities related to data collection from various bibliographic sources. The results of this study show that an interdisciplinary approach in Social Science (IPS) can offer a more comprehensive understanding of the dynamics of society and the environment. Integrating perspectives from history, sociology, anthropology, geography, economics, politics, and law enriches social analysis and clarifies the interconnections between various social phenomena. This study also recommends that in teaching IPS, the integration of other social science disciplines should be strengthened to produce a more holistic and practical understanding in the context of everyday life.